2002
DOI: 10.1063/1.1499985
|View full text |Cite
|
Sign up to set email alerts
|

Growth model and the effect of CuO nanocrystallites on the properties of chemically derived epitaxial thin films of YBa2Cu3O7−x

Abstract: Articles you may be interested inDouble-sided reel-to-reel metal-organic chemical vapor deposition system of YBa2Cu3O7-δ thin films J. Vac. Sci. Technol. A 32, 041512 (2014); 10.1116/1.4884367 4-fold enhancement in the critical current density of YBa2Cu3O7 films by practical ion irradiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…On the other hand, the longer duration of the heat treatment (1) causes CuO nanocrystallites growth. The growth results in a decent of value [7]. The effect of the growth on value is also illustrated in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, the longer duration of the heat treatment (1) causes CuO nanocrystallites growth. The growth results in a decent of value [7]. The effect of the growth on value is also illustrated in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Calcining process, however, has not thoroughly been studied yet. In our recent work, the decomposition of trifluoroacetates [7]. reaches a maximum at around 10 hours of the decomposition time during the heat treatment of 200 to 250 C. Origin of this peak formation is tentatively explained as effects of decomposed residue such as carbon content and CuO grain growth.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The defects could behave as flux pinning sites, and thus Jc is enhanced. gradually [34,35]. Since the amorphous LAO area is smaller, the Ostwald ripening mechanism would make the top YBCO maintain its primitive growth characteristics, as shown in Figure 6f and the corresponding schematic diagram in Figure 8.…”
Section: Mechanism Of the J C Variationmentioning
confidence: 99%
“…The partial pressure of water, oxygen, the concentration of HF and temperature are main factors in the YBCO nucleation and growth. It has been suggested that reducing the fluorine content in the metal-organic precursors could help to lessen inhomogeneity in the resulting films [1,2] and the growth rate of the YBCO film is governed by Temperature, P H2O and P HF [3,4]. Takeshi Araki et al found that Y, Ba, and Cu trifluoroacetates decomposed to oxides or oxy-fluorides at 400°C in a humidified oxygen atmosphere, while Y and Ba trifluoroacetates which finally decompose to amorphous oxy-fluorides [5].…”
Section: Introductionmentioning
confidence: 99%